2004
DOI: 10.1128/iai.72.4.2002-2013.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lon Protease Activity Causes Down-Regulation of Salmonella Pathogenicity Island 1 Invasion Gene Expression after Infection of Epithelial Cells

Abstract: Salmonella enterica serovar Typhimurium causes self-limiting gastroenteritis in humans and a typhoid-like disease in mice that serves as a model for typhoid infections in humans. A critical step in Salmonella pathogenesis is the invasion of enterocytes and M cells of the small intestine via expression of a type III secretion system, encoded on Salmonella pathogenicity island 1 (SPI-1), that secretes effector proteins into host cells, leading to engulfment of the bacteria within large membrane ruffles. The in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
78
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 68 publications
8
78
1
Order By: Relevance
“…Similar results were observed when 100 mM NaCl was replaced with 200 mM sucrose (data not shown). These results are consistent with previous reports indicating that HilA, HilC, and HilD regulate SPI1 gene transcription and that HilC and HilD activate hilA transcription equally (3,7,8,9,10,11,19,33,34,37,40,41,47,49). To determine if the salt response required HilC and HilD equally, we performed an epistasis analysis.…”
Section: Rationalesupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were observed when 100 mM NaCl was replaced with 200 mM sucrose (data not shown). These results are consistent with previous reports indicating that HilA, HilC, and HilD regulate SPI1 gene transcription and that HilC and HilD activate hilA transcription equally (3,7,8,9,10,11,19,33,34,37,40,41,47,49). To determine if the salt response required HilC and HilD equally, we performed an epistasis analysis.…”
Section: Rationalesupporting
confidence: 91%
“…In contrast, the network responsible for controlling expression, assembly, and function of the SPI1 T3SS is still being actively investigated. It is quite clear that HilA is the proximal activator of SPI1 genes (4,7,8,26,33,34,43,49) and that hilA transcription is controlled by two other regulators, HilD and HilC (3,9,10,11,19,37,39,41,42,47,52). These regulators, in turn, have been reported to be controlled by four two-component signal transduction pathways.…”
mentioning
confidence: 99%
“…The ferric uptake regulatory protein, Fur, and the BarA/SirA two-component system are SPI-1 activators (Fortune et al 2006;Ellermeier and Slauch 2008). In turn, HilE (Fahlen et al 2000) and Lon (Takaya et al 2003;Boddicker and Jones 2004) are negative regulators of SPI-1.…”
mentioning
confidence: 99%
“…Bacterial histone-like proteins have similar DNA-binding extensions (54,55), and three (hupA (56), stpA (57), and ymoA (58)) are known Lon substrates. Paradoxically, although Lon down-regulates the expression of invasion genes and the efficiency of host-cell invasion (59,60), the study of Lon-null mutants has demonstrated that Lon is essential for systemic infection (61). Because the availability of nutrients within the phagosome is limited, ribosomal protein degradation may foster pathogenesis by generating much needed amino acids, thereby increasing the survivability of phagocytosed Salmonella.…”
Section: Fig 4 Cluster Analysis Of the Lc-ms Datamentioning
confidence: 99%